BUILDING UP THE STUDETS’ ENGLISH VOCABULARY TROUGH FANNY STORIES AT SMP NEGERI 2 DUAMPANUA KAB. PINRANG - Hernawati M. (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aims to improve the students’ English vocabulary through funny stories. The problem statement of the research was “Can Funny Stories Technique Build up the Students’ English Vocabulary at SMP Negeri 2 Duampanua?” The objective of the research was to find out whether or not the Funny Stories Technique is able to Build up the Students’ English Vocabulary. The researcher applied pre – experimental method with three steps, namely pre – test, treatment and post – test.The population was the students of SMP Negeri 2 Duampanua (academic year 2014 – 2015). There were four classes of the second year students and each class consists of 35 students so the member of population were 140 students. And the sampel technique sampling. It meant that, not all classes of the second year students of SMP Negeri 2 Duampanua Pinrang were taken as sampel, they are 30 students. The instrument of the research used was vocabulary test consist of pretest and posttest design. The descriptive analysis described students’ vocabulary achievement with mean score before treatment 30.83 and after treatment 63.16. This research result supported by the inferential statistics by using t – test. It is used to find out the significant difference between the results of the pre – test and post – test on vocabulary building using Funny Stories Technique. Thus, the value of the t – test is greater than t – table (14.96> 2.045). It means there is significant difference between the pretest and posttest of the students in vocabulary achievement after presenting the materials by using funny stories.